National study of the impact of rural immersion programs on intended location of medical practice in New Zealand - Yasmine Abid; Charlotte Connell; Branko Sijnja; Antonia Verstappen; Phillippa Poole (James Cook University, 2020)
Introduction: New Zealand (NZ) faces an ongoing shortage of rural medical professionals. In an effort to increase interest in rural practice, both of the medical schools in NZ offer rural immersion programs as well as rural entry pathways. The aim of this study was to compare the effect of long (>33-week) rural immersion with a short (5-week interprofessional) rural immersion or no rural immersion on the career location intentions of NZ medical students. Methods: This observational study used linked data from the Commencing Medical Students Questionnaire (CMSQ) and Exit Questionnaire (EQ), collected between 2011 and 2017 as part of the Medical Schools Outcomes Database project, along with information on whether or not a student undertook a rural immersion program. The main outcome measure was EQ career location intention (Rural (population 100 000)). The explanatory variables were rural immersion (long, short, none), age, ethnicity, background, CMSQ career location intention, gender, specialisation preferences and interest in rural medicine. In addition to univariate analysis, data were used to build a multinomial model to determine relative associations of these variables with the outcome. Results: Full data were available for 1367 NZ medical students (47% of all students during the time period). Of these, 17.4% had undertaken a long or short rural immersion program. In univariate analysis, age was the only variable that did not significantly predict EQ rural intention outcome. In the multivariate model, rural immersion was a significant independent predictor of EQ career location intention. Students taking a long rural immersion were 6.4 and 4.4 times more likely to select a Rural or Regional intention, respectively, than those with no rural immersion. This strong effect on rural intentions was seen regardless of background. CMSQ career location intention, background, ethnicity, rural club membership and preference for general practice were also significant predictors. While short rural immersion did not have an independent effect, this finding should be interpreted with caution given the smaller number of students and the response rate. Conclusions: Long rural immersion is highly beneficial for increasing interest in rural work, increasing the likelihood that medical students will intend to work outside an urban setting. Students who signal an early rural intention are strong candidates for such programs later in their course, regardless of their background. A three-category classification for geographic background and career location intention permitted a more detailed understanding of the interplay among demographic variables and rural immersion in influencing career intentions. Following cohorts into their postgraduate years is needed to ascertain if these career location intentions persist.